Teste e seleção de produtos para tratamento de água produzida e água para geração de vapor. - Souza, Valécia Dantas de (Universidade Federal Rural do Semi-Árido, 2019)
The need for rationalization of water in various sectors that use it has made recurring the reuse of materials and the application of methods for the use of such materials and / or waste in production systems. Within the industry there are companies and professionals specializing in materials management focused on increasing efficiency and using or applying new technologies. Thus, this report presents the practices carried out in a curricular internship format performed at Agena Resinas e Colas LTDA, a company that was founded seeking excellence in the manufacture of chemical solutions for industry, aiming to solve process problems with the development and production of additives. chemicals and specialty products for the oil industry. The apprenticeship was carried out in the oil sector, where it seeks to select and improve chemical solutions for water treatment in the various stages of the process. The focus was on water treatment, as it is a growing sector in which it is desired to optimize effluent treatment efficiency. During the professional practice, formula verification activities were performed for two types of effluents: water produced from a Potiguar Basin field and water taken from a local river for steam generation. The tests aim to verify the functionality of ready-to-use industrial polymers, product selection that presents better visual efficiency with subsequent measurement of treatment parameters such as dosages, dilutions and visual quality verification aiming at further specification of treated water in required parameters. In the end it was possible to verify different methodologies for each type of effluent in order to achieve results that explain the operation of the formulas and the solutions created as a viable alternative for industry, based on the know-how and market experiences of the company. It was possible to observe how the work of a specialty chemicals industry can add value to the industry by generating less waste, increasing process efficiency and creating business opportunities with waste material. The experience contributed to the understanding of the application of the theories seen in the academy and the approach of a niche market to which the petroleum engineer can be introduced, developing skills and broadening the vision for the job market, positively impacting the formation.
Relatório
Keywords: Agena; Petróleo; Indústria; Efluente; Processo; Especialidades químicas; Agena; Petroleum; Industry; Effluent; Process; Chemical specialties; ENGENHARIAS::ENGENHARIA DE PETROLEO